2012
DOI: 10.1680/warm.11.00014
|View full text |Cite
|
Sign up to set email alerts
|

Oxodegradable plastics: degradation, environmental impact and recycling

Abstract: This paper summarises the results of a study to assess the environmental impact of oxo-degradable plastics. These plastics are mainly based on polyethylene and contain additives that cause the plastic to undergo oxidative degradation by a process accelerated by light and/or heat. The approach used in the study has been to review the published research on oxo-degradable plastics, assess other literature available in the public domain, and also to engage with stakeholders throughout the life cycle of the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
0
36
0
2
Order By: Relevance
“…As a result, the study on environmentally friendly plastics became the interest of many research groups. [16][17][18] From the literature, it is suggested that the oxo-materials could reduce the degradability time of the plastics to 2-5 years in the United Kingdom. In the first method, plastics are made from renewable feedstocks such as polyhydroxyalkanoates and polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, the study on environmentally friendly plastics became the interest of many research groups. [16][17][18] From the literature, it is suggested that the oxo-materials could reduce the degradability time of the plastics to 2-5 years in the United Kingdom. In the first method, plastics are made from renewable feedstocks such as polyhydroxyalkanoates and polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] There are two main strategies to develop biodegradable plastics. 18 The mechanism of degradation of polyethylene was reported by Thomas et al 18 In the first step, polyethylene is oxidized as below: Using this strategy can reduce greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The imminent degradation, as a result of the action of oxo-degradable additives, has made these types of material nonrecyclable [20]. Also, the lifespan of the oxo-degradable polyolefins depends on polymeric chains (unsaturated or branched) and their susceptibility to capture oxygen.…”
Section: Introductionmentioning
confidence: 99%